2017
DOI: 10.1111/odi.12793
|View full text |Cite
|
Sign up to set email alerts
|

GREM2 nucleotide variants and the risk of tooth agenesis

Abstract: Our study confirmed that GREM2 is a candidate gene for tooth agenesis, which mutations can explain, however, only a small fraction of the genetic contribution to the pathogenesis of this anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…GREM2 variants were suggested as likely pathogenic for tooth agenesis and other dental anomalies such as taurodontism and microdontia, although incomplete penetrance and variable expressivity even within the same families were reported . Our association findings also support a role for this gene in isolated tooth agenesis and tooth development.…”
Section: Discussionsupporting
confidence: 66%
“…GREM2 variants were suggested as likely pathogenic for tooth agenesis and other dental anomalies such as taurodontism and microdontia, although incomplete penetrance and variable expressivity even within the same families were reported . Our association findings also support a role for this gene in isolated tooth agenesis and tooth development.…”
Section: Discussionsupporting
confidence: 66%
“…ATF1 , WNT10B and GREM2 were recently suggested as candidate genes for TA, 5,8,16 and replicated in independent studies 4,17,18 . In this study, we assessed the potential allele‐specific effects of the TA‐associated variants ATF1 rs11169552, WNT10B rs833843 and GREM2 rs1414655, located in the regulatory regions of their respective genes.…”
Section: Discussionmentioning
confidence: 94%
“…Human genome-wide association studies (GWAS) identified GREM2 variants associated with developmental disorders and disease, such as bone function and bone mass associated with osteoporosis, atrial fibrillation, and tooth agenesis (9)(10)(11)(12)(13). A Grem2 -/mouse line was previously developed as part of a high-throughput mouse knockout and phenotyping project (14).…”
Section: Introductionmentioning
confidence: 99%
“…GREM2 tightly associates with heparin through a protein binding domain outside of the BMP binding domain, which limits or downregulates BMP signaling, thus enhancing the inhibitory activity of GREM2 on BMPs (2,8). Human genome-wide association studies (GWAS) identified GREM2 variants associated with developmental disorders and disease, such as bone function and bone mass associated with osteoporosis, atrial fibrillation, and tooth agenesis (9)(10)(11)(12)(13). A Grem2 -/mouse line was previously developed as part of a high-throughput mouse knockout and phenotyping project (14).…”
Section: Introductionmentioning
confidence: 99%